The application of gastrointestinal endoscopy in children: a narrative review - Zhang, Guo; Zhao, Guiping; Li, Peng; Zhang, Shutian (Frontiers in Pediatrics, 2025)
Digestive endoscopy in children is increasingly used for the diagnosis and treatment of a broad range of diseases affecting the stomach, intestines, biliary tract, and pancreas, with the advantages of being minimally invasive and efficient. Endoscopic procedures in children differ from those in adults in terms of both indications and primary objectives. Furthermore, ensuring the safety and comfort of children during the examination necessitates additional considerations, such as the use of appropriately sized endoscopes, carefully tailored sedation protocols, and bowel preparation regimens. This article provides an overview of the diagnostic value of endoscopy in common digestive tract diseases and challenging conditions in children, and it details the clinical applications of various endoscopic therapeutic techniques. Furthermore, the review focuses on several core aspects of endoscopy in children, including age-stratified selection strategies for endoscopic instruments, safety evaluations of sedation and anesthesia protocols, indications and contraindications for various endoscopic techniques, potential procedure-related adverse events, as well as current disparities in the development of endoscopy in children across different regions. Despite substantial progress in the field, challenges remain, including the lack of specialized devices, technical complexity, and gaps in operator training and quality control. Future efforts should emphasize multicenter studies, the development of standardized operating guidelines, and the integration of artificial intelligence and novel imaging technologies to optimize the endoscopy diagnostic and therapeutic system, thereby advancing digestive endoscopy in children toward greater precision, safety, and efficiency.